Delusions of Certainty: Commercial Vessel COVID-19 Risk Stratification. Issue 4 (4th August 2021) - Codreanu, Tudor A.; Armstrong, Paul K.
Abstract: Since the World Health Organization's (WHO's) pandemic declaration on March 11, 2020, coronavirus disease 2019 (COVID-19) outbreaks have occurred on numerous maritime vessels and the containment measures, travel restrictions, and border closures continue to make it increasingly difficult for ship operators world-wide to be granted pratique, conduct trade, and conduct crew changes. Knowledge of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) circulating on-board a ship prior to its arrival has significant implications for the protection of shore-based maritime workers (ie, pilots, stevedores, and surveyors), the broader community, and trade. A useful approach is a graded assessment of the public health risk. The Western Australia (WA) experience and associated observed pitfalls in implementing the prediction equation for the potential presence of SARS-CoV-2 on-board based on five COVID-19 outbreaks on commercial and cruise vessels during 2020 is described. Despite best efforts, the qualitative and quantitative predictors of SARS-CoV-2 circulating on-board commercial vessels are failing to deliver the required certainty, and to date, the only accepted method of ascertaining the presence of SARS-CoV-2 remains the real-time reverse transcription polymerase chain reaction (rRT-PCR) testing reported by an accredited laboratory. Based on legal or regulatory requirements, germane processes, underpinned by robust and auditable processes and procedures, must be put in place to inform the risk assessment of SARS-CoV-2 circulating on-board vessels.